Qiliqiangxin Modulates the Gut Microbiota and NLRP3 Inflammasome to Protect Against Ventricular Remodeling in Heart Failure - Yingdong Lu; Mi Xiang; Laiyun Xin; Laiyun Xin; Yang Zhang; Yang Zhang; Yuling Wang; Zihuan Shen; Li Li; Xiangning Cui (Frontiers in Pharmacology, 2022)
Aims: Pathological left ventricular (LV) remodeling induced by multiple causes often triggers fatal cardiac dysfunction, heart failure (HF), and even cardiac death. This study is aimed to investigate whether qiliqiangxin (QL) could improve LV remodeling and protect against HF via modulating gut microbiota and inhibiting nod-like receptor pyrin domain 3 (NLRP3) inflammasome activation.Methods: Rats were respectively treated with QL (100 mg/kg/day) or valsartan (1.6 mg/kg/day) by oral gavage after transverse aortic constriction or sham surgery for 13 weeks. Cardiac functions and myocardial fibrosis were assessed. In addition, gut microbial composition was assessed by 16S rDNA sequencing. Furthermore, rats’ hearts were harvested for histopathological and molecular analyses including immunohistochemistry, immunofluorescence, terminal-deoxynucleotidyl transferase-mediated 2’-deoxyuridine 5’-triphosphated nick end labeling, and Western blot.Key findings: QL treatment preserved cardiac functions including LV ejection fractions and fractional shortening and markedly improved the LV remodeling. Moreover, HF was related to the gut microbial community reorganization like a reduction in Lactobacillus, while QL reversed it. Additionally, the protein expression levels like IL-1β, TNF-α, NF-κB, and NLRP3 were decreased in the QL treatment group compared to the model one.Conclusion: QL ameliorates ventricular remodeling to some extent in rats with HF by modulating the gut microbiota and NLRP3 inflammasome, which indicates the potential therapeutic effects of QL on those who suffer from HF.